2022
DOI: 10.1039/d2tc01150f
|View full text |Cite
|
Sign up to set email alerts
|

Conducting polymers with redox active pendant groups: their application progress as organic electrode materials for rechargeable batteries

Abstract: This review summarizes the application progress of conducting redox polymers with energy storage capability for different types of rechargeable batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 181 publications
0
8
0
Order By: Relevance
“…To accomplish the mechanisms of side-reaction suppression and dead Na reutilization, the requirements of an electroconductive electrolyte are as follows: (1) high ionic conductivity, (2) high chemical stability with cell components, (3) higher redox voltage than Na/Na + reaction voltage (−2.71 V vs SHE), and (4) enough electronic conductivity to reutilize the dead Na. To satisfy these requirements, several candidates were chosen among the conducting polymers and polycyclic aromatic redox-active materials. In this study, Sat.Na biphenyl–DME electrolyte was mainly tested due to its high stability with NASICON solid electrolyte, higher redox voltage (∼0.09 V vs Na), and high chemical stability with glyme-based solvents. , In previous studies, it has been reported that NaBP material can be used as a liquid anode or anolyte with a specific capacity (∼30 mAh/mL) and additional Na-metal plating with a small amount (<0.5 mAh/cm 2 ); however, the role of electroconductivity in electrolytes was not demonstrated. , As shown in Scheme b, the transported electrons from the current collector to NaBP cannot induce the decomposition of the electrolyte due to the redox reaction during charging. In addition, the presodiated NaBP can suppress the side reactions of residual moisture, even with the addition of high-reactivity Na-ion transport salts.…”
Section: Resultsmentioning
confidence: 99%
“…To accomplish the mechanisms of side-reaction suppression and dead Na reutilization, the requirements of an electroconductive electrolyte are as follows: (1) high ionic conductivity, (2) high chemical stability with cell components, (3) higher redox voltage than Na/Na + reaction voltage (−2.71 V vs SHE), and (4) enough electronic conductivity to reutilize the dead Na. To satisfy these requirements, several candidates were chosen among the conducting polymers and polycyclic aromatic redox-active materials. In this study, Sat.Na biphenyl–DME electrolyte was mainly tested due to its high stability with NASICON solid electrolyte, higher redox voltage (∼0.09 V vs Na), and high chemical stability with glyme-based solvents. , In previous studies, it has been reported that NaBP material can be used as a liquid anode or anolyte with a specific capacity (∼30 mAh/mL) and additional Na-metal plating with a small amount (<0.5 mAh/cm 2 ); however, the role of electroconductivity in electrolytes was not demonstrated. , As shown in Scheme b, the transported electrons from the current collector to NaBP cannot induce the decomposition of the electrolyte due to the redox reaction during charging. In addition, the presodiated NaBP can suppress the side reactions of residual moisture, even with the addition of high-reactivity Na-ion transport salts.…”
Section: Resultsmentioning
confidence: 99%
“…Conjugated conductive polymers such as polythiophene, polyaniline, polyacetylene, and polypyrrole have developed rapidly due to their poor solubility and high electrical conductivity (10 −5 -100 S cm −1 ). [39][40][41] Conductive polymers are oxidized (doped with anions) or reductively doped (doped with cations) to achieve energy storage. Anion-doped conducting polymers usually exhibit high redox potentials (>3.5 V versus Li/Li + ).…”
Section: Conductive Polymersmentioning
confidence: 99%
“…Thus, existing theoretical description is not easily applicable to the hybrid types of electroactive polymers, which possess both types of charge carriers and both charge transfer mechanisms. [76][77][78][79][80] To the best of our knowledge, thermodynamics based theoretical descriptions of conducting redox polymers have not yet been proposed. Here we present a study of three recently discovered CRPs: pDiTS, pMTS and pPyT (the structures of their monomers are represented in Chart 1).…”
Section: Introductionmentioning
confidence: 99%